2019
DOI: 10.1177/0267659119855853
|View full text |Cite
|
Sign up to set email alerts
|

Use of bivalirudin as a primary anticoagulant in a child during Berlin Heart EXCOR ventricular assist device support

Abstract: We describe our experience of bivalirudin use, a newer direct thrombin inhibitor, in an infant who was supported with Berlin Heart EXCOR VAD (Berlin VAD) as bridge to transplant for 122 days without complications and without need for pump exchange. An 11-month-old girl with dilated cardiomyopathy with acute heart failure was awaiting cardiac transplant. Lack of improvement despite maximizing medical therapy and anticipating a prolonged waitlist time, she was supported with Berlin LVAD as a bridge to transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Target aPTT variable (range 50–100 s) Major bleeding events occurred in 7 pts with 8 overall bleeding events (6 pts on bivalirudin, 1 on argatroban); all pts were on antiplatelet agent at time of bleeding event. Pump thrombosis event rate of 5.7 per 1000 pt days of support; neurologic event rate of 2.1 per 1000 pt days of support on bivalirudin Campbell et al [ 20 ] 19 pediatric pts on bivalirudin for VAD (9 pts with BiVAD, 5 pts with LVAD, 5 pts with RVAD) Retrospective analysis Initial median (IQR) infusion rate 0.1 (0.1–0.2) mg/kg/h; average infusion rate 0.4 (0.31–1) mg/kg/h; maximum median (IQR) infusion rate of 0.7 (0.41–1.2) mg/kg/h; target aPTT 60–90 s Average percentage of time spent within goal aPTT range was 67.4%; higher average and maximum dose vs. pts on ECMO; similar initial dose used Medar et al [ 29 ] 11-month-old girl with dilated cardiomyopathy utilizing LVAD as bridge to transplant (122 days of support) Case report No bivalirudin bolus reported; initial infusion rate 0.15 mg/kg/h; maintenance rate ranged from 0.15 to 2.3 mg/kg/h; target aPTT 60–90 s No evidence of thrombus or need for pump change; no significant bleeding intraoperatively or postoperatively. Pt discharged home on postoperative day 15 ACT activated clotting time, aPTT activated partial thromboplastin time, BiVAD biventricular assist device, DTI direct thrombin inhibitor, ECLS extracorporeal life support, ECMO extracorporeal membrane oxygenation, FFP fresh frozen plasma, GI gastrointestinal, HIT heparin-induced thrombocytopenia, LVAD left ventricular assist device, PS propensity score, pt(s) patient(s), RBC red blood cells, RVAD right ventricular assist device, SDH subdural hematoma, UFH unfractionated heparin, VAD ventricular assist device, VAP ventilator-associated pneumonia …”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Target aPTT variable (range 50–100 s) Major bleeding events occurred in 7 pts with 8 overall bleeding events (6 pts on bivalirudin, 1 on argatroban); all pts were on antiplatelet agent at time of bleeding event. Pump thrombosis event rate of 5.7 per 1000 pt days of support; neurologic event rate of 2.1 per 1000 pt days of support on bivalirudin Campbell et al [ 20 ] 19 pediatric pts on bivalirudin for VAD (9 pts with BiVAD, 5 pts with LVAD, 5 pts with RVAD) Retrospective analysis Initial median (IQR) infusion rate 0.1 (0.1–0.2) mg/kg/h; average infusion rate 0.4 (0.31–1) mg/kg/h; maximum median (IQR) infusion rate of 0.7 (0.41–1.2) mg/kg/h; target aPTT 60–90 s Average percentage of time spent within goal aPTT range was 67.4%; higher average and maximum dose vs. pts on ECMO; similar initial dose used Medar et al [ 29 ] 11-month-old girl with dilated cardiomyopathy utilizing LVAD as bridge to transplant (122 days of support) Case report No bivalirudin bolus reported; initial infusion rate 0.15 mg/kg/h; maintenance rate ranged from 0.15 to 2.3 mg/kg/h; target aPTT 60–90 s No evidence of thrombus or need for pump change; no significant bleeding intraoperatively or postoperatively. Pt discharged home on postoperative day 15 ACT activated clotting time, aPTT activated partial thromboplastin time, BiVAD biventricular assist device, DTI direct thrombin inhibitor, ECLS extracorporeal life support, ECMO extracorporeal membrane oxygenation, FFP fresh frozen plasma, GI gastrointestinal, HIT heparin-induced thrombocytopenia, LVAD left ventricular assist device, PS propensity score, pt(s) patient(s), RBC red blood cells, RVAD right ventricular assist device, SDH subdural hematoma, UFH unfractionated heparin, VAD ventricular assist device, VAP ventilator-associated pneumonia …”
Section: Resultsmentioning
confidence: 91%
“…The initial infusion rate of 0.3 mg/kg/h utilized by both VanderPluym et al [ 28 ] and Bates et al [ 25 ], case series reports of 43 and 14 pediatric patients, respectively, was identical to that of Nagle et al [ 7 ] and Ezetendu et al [ 17 ]. Meanwhile, in a case report by Medar et al [ 29 ], the authors stated an initial bivalirudin infusion rate of 0.15 mg/kg/h, 50% that of VanderPluym et al [ 28 ] and Bates et al [ 25 ]. Campbell et al [ 20 ] reported that the median initial rate was similar between VAD and ECMO patients, at 0.1 mg/kg/h.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations